Distributed Denial of Service Attacks and Defense Mechanisms. (October 2019) - Tang, Dan; Kuang, Xiaohong
Abstract: Distributed denial-of-service (DDoS) attacks have become a common problem in networked environments. The large number of variations in both the types of DDoS attacks and their mitigating approaches are an apt indicator of the extent of the issue. This article will offer an analysis of the existing DDoS attacks and their corresponding countermeasures. The paper aims to highlight the strengths and weaknesses of the available defenses in order to demonstrate the degree of applicability and efficiency of the solution methodologies. To achieve these objectives, the paper assumes a systematic design whereby it evaluates the DDoS attacks according to similar attributes, which in turn informs the evaluation of defense tactics.